Table of Content - - (Journal of engineering sciences and information technology, 2025)
:Table of Content • The impact of the Vision 2030 projects on contemporary architecture: Analytical study of Saudi architecture map Eng. Nazar Mohamed Elkheir Mohamed Osman • Surface Analysis Using Cloud Computing: An Applied Study on the Google Earth Engine Platform Dr. Nadiah Awad Al-Safri • Smart Tourism and Environmental Sustainability: A Descriptive and Analytical Case Study of Saudi Arabia Eng. Ashraf Fawzy Hassan • Integration of Industrial and Surgical Robotic Systems: A Case Study of Combining the SCARA Robot with the Da Vinci Robot Asst-Prof. Lara Fathi Kadid, Lecturer. Hasan Khaled Kazzaz, Eng. Mohamad Adib Mohamad Taki Eddin Issa • Smart Recommendation System for Tourists Nour Abd Alhameed Khallof, Dr. Majida Albakoor